LEGAL REVIEW OF CONSUMER LAW PROTECTION ON PERSONAL DATA ON DIGITAL PLATFORM - Arfi Azhari (Faculty of Law, Universitas Lampung, 2021)
Legal protection for consumers must be considered because the existence of consumers is prone to fraud. Personal consumer data protect one form of legal protection for consumers in conducting transactions with business actors, both domestic and foreign transactions. With the times at this time, consumer data that exists on business actors, both in the form of state-owned enterprises or business actors in the private form, is a lot of consumer data that these business actors trade and this consumer data is widely known. The problem studied is how the consumer’s legal protection of personal data on digital platforms. Research methods are using normative research methods, namely by explaining the issues and views of consumer legal protection of personal data on existing legal regulatory, digital platforms. The results illustrate that for now, consumer legal protection of personal data on digital platforms still refers to several laws and regulations in Indonesia. The government is also preparing a Draft Law on Personal Data Protection, which will become lex specialis. For the protection of personal consumer data in Indonesia related to personal data on digital platforms.